Indoor ranging and localisation algorithm based on received signal strength indicator using statistic parameters for wireless sensor networks. (1st October 2015) - Pagano, Saverio; Peirani, Simone; Valle, Maurizio
Abstract : This paper addresses the implementation of indoor real‐time localisation system (RLTS) using wireless sensor networks. A RLTS consists of anchor nodes (i.e. nodes with fixed and known locations), beacon nodes and a location engine: the beacon node to be localised sends a packet which is captured from some anchor nodes, the anchor nodes forward the information extracted from the packet to the location engine for the estimation of the position of the transmitting beacon node. The authors present an algorithm that achieves beacon node localisation accuracy of a few metres in indoor environments. The algorithm is based on two steps: in the first step, the algorithm computes the ranging between anchor nodes and beacon node, in the second one, the algorithm estimates the beacon node localisation. The received signal strength indicator (RSSI) is used for the ranging estimation. The proposed approach avoids dedicated and expensive devices, which are used for the synchronisation between beacon and anchor nodes, to compute the time‐of‐flight of the signal. The authors introduce a confidence parameter for improving accuracy (based on the standard deviation of the RSSI), and an anchor nodes selection strategy for tackling the problem of non‐line‐of‐sight communication between nodes.